Super-Cripple Sights: Disable Heroes in Raymond Carver's Cathedral and Sophocles' Oedipus Rex - Lungeli, Dipak (SCHOLARS: Journal of Arts & Humanities, 2021)
Robert and Tiresias, disable protagonists respectively of Raymond Carver's Cathedral and Sophocles' Oedipus Rex with their super cripple qualities challenge the imperatives of ableist ideals. Protagonists’ blindness leads them to insight whereas their counter characters’ sight leads them to darkness. Such a role reversal leads to a questioning of dichotomies and establishes an alternative view to the definition of blindness and insight. To support this claim, I use Lennard J. Davis’ concept of disable bodies in literature, Rod Michalko’s notion of fictional explorations of disability, and Nickianne Moody’s model of disability informed criticism backed up by Judith Butler’s notion of body politics, Rosemarie Thompson’s idea of extraordinary bodies, and different critical readings on body. This framework of interpretation validates disable bodies as cultural construction. It also regards literatureas apt venue to challenge culturally assigned definition of ability and disability in favor of new body possibilities. The theoretical framework thus discovers Carver and Sophocles redrawing the concept of able-bodiedness and deeply rooted cultural hierarchies like able/disable, sight/blind, sight/insight, body/mind, visible/invisible, and inside/outside in their literary texts.